2018
DOI: 10.1073/pnas.1813451115
|View full text |Cite
|
Sign up to set email alerts
|

Redox, amino acid, and fatty acid metabolism intersect with bacterial virulence in the gut

Abstract: The gut metabolic landscape is complex and is influenced by the microbiota, host physiology, and enteric pathogens. Pathogens have to exquisitely monitor the biogeography of the gastrointestinal tract to find a suitable niche for colonization. To dissect the important metabolic pathways that influence virulence of enterohemorrhagicEscherichia coli(EHEC), we conducted a high-throughput screen. We generated a dataset of regulatory pathways that control EHEC virulence expression under anaerobic conditions. This u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…In contrast, the PmrA/B response of C. burnetii is not linked to metabolic changes but to transition to a virulent phenotype. Transcriptional virulence induction in response to amino acids also appears true for enterohemorrhagic Escherichia coli (EHEC) as a recent report indicated that exogenous cysteine can be sensed by the EHEC cysteine utilization regulator CutR, leading to increased expression of genes within the virulence-associated locus of the enterocyte effacement pathogenicity island (61).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the PmrA/B response of C. burnetii is not linked to metabolic changes but to transition to a virulent phenotype. Transcriptional virulence induction in response to amino acids also appears true for enterohemorrhagic Escherichia coli (EHEC) as a recent report indicated that exogenous cysteine can be sensed by the EHEC cysteine utilization regulator CutR, leading to increased expression of genes within the virulence-associated locus of the enterocyte effacement pathogenicity island (61).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of metabolic regulators that display dual-functional roles as they pertain to controlling virulence have been previously reported in a number of pathogens. It was recently shown that Citrobacter rodentium, the surrogate in vivo model organism for enterohemorrhagic Escherichia coli, uses an intricate circuit of amino and fatty acid regulators to control the expression of virulence genes in the infected gut (37). Additionally, the intracellular pathogen Listeria monocytogenes uses the branched-chain amino acid sensor CodY to directly control the activity of the master virulence regulator prfA (38).…”
Section: Discussionmentioning
confidence: 99%
“…using the Ashwell pathway, which is under the control of the ExuR transcriptional regulator 9,10 . A high throughput screen for metabolic pathways and transcriptional factors that regulate LEE gene expression identified ExuR as a LEE regulator 13 . ExuR is a member of the GntR family of transcriptional regulators 14 , has been previously characterized as a regulator of sugar acid catabolism in E. coli 15,16 , and is responsive to galacturonic-acid [17][18][19] .…”
mentioning
confidence: 99%